Lactate is useful for the efficient replication of porcine epidemic diarrhea virus in cell culture - Wuri, Nile; Gou, Hongchao; Zhang, Bin; Wang, Menglu; Wang, Songqi; Zhang, Weixiao; He, Haiyan; Fan, Xuelei; Zhang, Chunhong; Liu, Zhicheng; Geri, Letu; Shen, Haiyan; et al. (Frontiers in Veterinary Science, 2023)
Porcine epidemic diarrhea virus (PEDV) is a deadly pathogen infecting pig herds, and has caused significant economic losses around the world. Vaccination remains the most effective way of keeping the PEDV epidemic under control. Previous studies have shown that the host metabolism has a significant impact on viral replication. In this study, we have demonstrated that two substrates of metabolic pathway, glucose and glutamine, play a key role in PEDV replication. Interestingly, the boosting effect of these compounds towards viral replication appeared to be dose-independent. Furthermore, we found that lactate, which is a downstream metabolite, promotes PEDV replication, even when added in excess to the cell culture medium. Moreover, the role of lactate in promoting PEDV was independent of the genotype of PEDV and the multiplicity of infection. Our findings suggest that lactate is a promising candidate for use as a cell culture additive for promoting PEDV replication. It could improve the efficiency of vaccine production and provide the basis for designing novel antiviral strategies.